Development of the Ukrainian national idea: historical evolution in the first half of the twentieth century - Макарова, А. Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article concerns the historical path of Ukrainian nationalism from the very beginning of the idea of national independency to the period of armed resistance. Furthermore, the transition from the idealistic and peaceful way of building a Ukrainian state to the ideologically grounded necessity of creating militant organizations is examined. We believe that this would help to understand the problems of Ukrainian national idea, to find errors and to make an effort to correct them in the future.